The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1182/blood.v114.22.866.866
|View full text |Cite
|
Sign up to set email alerts
|

TG-0054, a Novel and Potent Stem Cell Mobilizer, Displays Excellent PK/PD and Safety Profile in Phase I Trial.

Abstract: 866 Background: Stem cells are retained in the bone marrow via the trophic effects of the binding of chemokine stromal cell-derived factor-1α (SDF-1α) to its receptor, CXC chemokine receptor 4 (CXCR4). TG-0054 inhibits SDF-1α/CXCR4 binding and therefore mobilizes stem cells into peripheral blood. Animal studies in mice showed rapid and effective mobilization of CD34+ hematopoietic stem cells (HSCs) and CD133+ endothelial progenitor cells (EPCs) into periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Phase I clinical trials revealed that single-dose administration of the antagonist more than increased the number of circulating stem cells to the numbers required for a successful transplant. 213 Phase 1 results also indicated that TG-0054 may be given as a monotherapy in contrast to 36 that is given with granulocyte macrophage colony stimulating factor (GM-CSF). Currently the antagonist is undergoing several phase II clinical trials for the treatment of multiple myeloma and non-Hodgkin's lymphoma.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Phase I clinical trials revealed that single-dose administration of the antagonist more than increased the number of circulating stem cells to the numbers required for a successful transplant. 213 Phase 1 results also indicated that TG-0054 may be given as a monotherapy in contrast to 36 that is given with granulocyte macrophage colony stimulating factor (GM-CSF). Currently the antagonist is undergoing several phase II clinical trials for the treatment of multiple myeloma and non-Hodgkin's lymphoma.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…Receptor binding studies revealed potencies for CXCR4 ranging from 4 to 100 nM, and a prototypical structure is shown ( 37 , Figure ). Phase I clinical trials revealed that single-dose administration of the antagonist more than increased the number of circulating stem cells to the numbers required for a successful transplant . Phase 1 results also indicated that TG-0054 may be given as a monotherapy in contrast to 36 that is given with granulocyte macrophage colony stimulating factor (GM-CSF).…”
Section: Chemokine Receptor Antagonistsmentioning
confidence: 99%
“…Examining these varied studies, an extension of plerixafor indications is to be expected in the coming years, as are new pharmacological alternatives. Indeed, new compounds targeting CXCR4 are in development: small molecules (TG-0054 [60,61,62]) such as plerixafor, but also peptides (BL-8040 [63], (BK)T140 [64], POL6326 [65], LY2510924 [66]), or oligonucleotides (NOX-A12 [67]). All have already been tested in humans as part of phase I or early phase II clinical trials.…”
Section: Resultsmentioning
confidence: 99%
“…To ensure that TG-0054, which was shown to mobilize HSCs in mice and humans (11, 22), was effective in mobilizing CXCR4+ stem cells in minipigs, we analyzed PB cell components after TG-0054 treatment (two intravenous doses of 2.85 mg/kg TG-0054 of 72 h apart). TG-0054 increased PB white blood cell (WBC) counts, which peaked at 0.5 and 1 h after the first dose and the second dose, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%